Ferroptosis in ocular diseases: mechanisms, crosstalk with other cell death pathways, and therapeutic prospects - Huang, Shuai; Sun, Yuying; Yu, Xinxin; Ren, Xuan; Wang, Lei; Sun, Yan; Deng, Aijun (Frontiers in Medicine, 2025)
BackgroundOcular diseases pose a significant threat to visual health, with ferritin ferroptosis playing a critical role in the pathogenesis of many such conditions. Ferritin accumulation, coupled with ferritin autophagy-mediated release of labile Fe2+, triggers iron-dependent lipid peroxidation and ferroptosis. These include disruptions in iron metabolism, oxidative stress imbalances, altered intracellular signaling, and changes to the local microenvironment. Such aberrant ferritin deposits not only compromise the structure and function of ocular cells but also accelerate disease progression. Ferroptosis, a newly recognized form of cell death characterized by iron-dependent lipid peroxidation, differs from traditional cell death mechanisms, including apoptosis.Materials and methodsThis review systematically evaluated the role of ferroptosis in ocular diseases using a predefined search strategy. In brief, PubMed was searched for studies published between 2012 and 2025 using keywords combining ferroptosis, ocular diseases, retinal, corneal etc. After excluding non-ocular studies and duplicates, 188 articles were included following a full-text review.ConclusionThis review examines the molecular mechanisms underlying ferroptosis and its implications for major ocular diseases. It explores how ferroptosis contributes to disease pathology in retinal diseases, offering novel insights for future therapeutic strategies. The potential for targeting ferroptosis pathways with iron modulators holds promise for advancing clinical treatments in ophthalmology.